2018
DOI: 10.1021/acs.jced.8b00581
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Toltrazuril and the Effect of a Cosolvent

Abstract: The purpose of this work is to study the dissolution process of toltrazuril and the influence of the solvent on solubility. In pure solvents, the solubility of toltrazuril increases with the increasing temperature, and the order of solubility data is as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Modified Jouyban−Acree Model. 14,15 The Jouyban− Acree model, shown in eq 6, links the solubility of 7-azaindole in pure solvents with temperature and can more accurately describes the solubility of 7-azaindole in binary solvents (Figure 7, Tables 7 and 8).…”
Section: Resultsmentioning
confidence: 99%
“…Modified Jouyban−Acree Model. 14,15 The Jouyban− Acree model, shown in eq 6, links the solubility of 7-azaindole in pure solvents with temperature and can more accurately describes the solubility of 7-azaindole in binary solvents (Figure 7, Tables 7 and 8).…”
Section: Resultsmentioning
confidence: 99%
“…10−12 Although Tol exhibits prominent pharmacological activities, its promising prospect is severely hampered by low aqueous solubility in the form of administration. 13,14 Some typical methods have been employed to improve the solubility and dissolution rate of Tol, such as solid dispersion, nanoemulsion, micronization, and cyclodextrin inclusion. 11,14,15 However, the stability and biocompatibility in these strategies have not yet met expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Toltrazuril (Tol, Figure a), an acclaimed broad-spectrum and high-efficiency anticoccidial drug, is broadly applied in the prophylaxis and treatment of diseases in pets, livestock, poultry, and also in humans caused by Cryptosporidium , Eimeria, and Isospora . Although Tol exhibits prominent pharmacological activities, its promising prospect is severely hampered by low aqueous solubility in the form of administration. , Some typical methods have been employed to improve the solubility and dissolution rate of Tol, such as solid dispersion, nanoemulsion, micronization, and cyclodextrin inclusion. ,, However, the stability and biocompatibility in these strategies have not yet met expectations. In Tol molecule, the cyanurate scaffold (ring Cg1) possesses a coplanar π-conjugated configuration, and the Cg2 and Cg3 rings feature the high electron density based on the electrostatic potential (ESP), which will be conducive to constructing aromatic interactions with π···X interactions (Figure b). , Meanwhile, due to the attracting electron effect of the carbonyl groups, the H atom riding on the N atom in the Cg1 ring is obviously weakly acidic and the N­(−H) atom becomes a stronger hydrogen bond donor. In addition, the rotatable σ bonds marked with red arrow in Figure a are prone to multiple configurations for packing.…”
Section: Introductionmentioning
confidence: 99%
“…In the above‐mentioned models, radiation in thermal response prediction for composites was mostly evaluated with regarding the surface emissivity as a constant or a function of temperature or totally ignored. [ 7–11 ] Recently, researchers [ 12,13 ] simulated the proportion of different energy consuming paths of ablative materials such as radiation, pyrolysis, conduction [ 14–19 ] and heat blockage. The results showed that the outward radiation gradually became the main way consuming energy with increasing temperature and porosity of material.…”
Section: Introductionmentioning
confidence: 99%